PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS IX.B SMP NEGERI 1 JAYAPURA - EKO SUPRAYITNO (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
The aims of this action research were: (a) to improve the learning process in the classroom (b) to find out how English learning outcomes increased after the STAD cooperative learning model was implemented. (c) Want to know the effect of the STAD cooperative learning model in increasing learning motivation towards English subject matter. This study used three rounds of classroom action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research was class IX.B students of SMP Negeri 1 Jayapura in 2022. The data obtained was in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I (52.00%) with the highest score of 80 and the lowest score of 50, cycle II (72.00%) with the highest score of 86 and the lowest score of 58, cycle III ( 92.00%) with the highest score of 92 and the lowest score of 70. While the class average value in cycle I was 71.60, Cycle II was 74.48 and Cycle III was 81.04. The conclusion of this study is that the STAD cooperative learning model can affect the learning motivation of Jayapura 1 Public Middle School students in 2022, and this learning model can improve student learning outcomes in class IX.B of Jayapura 1 Public Middle School ABSTRAKTujuan penelitian tindakan ini adalah: (a) Memperbaiki proses pembelajaran di kelas (b) Ingin mengetahui bagaimanakah peningkatan hasil belajar Bahasa Inggris setelah diterapkannya model pembelajaran kooperatif STAD. (c) Ingin mengetahui pengaruh model pembelajaran kooperatif STAD dalam meningkatkan motivasi belajar terhadap materi pelajaran Bahasa Inggris. Penelitian ini menggunakan penelitian tindakan kelas (classroom action research) sebanyak tiga putaran. Setiap putaran terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan, refleksi, dan refisi. Sasaran penelitian ini adalah Siswa kelas IX.B SMP Negeri 1 Jayapura Tahun 2022. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa hasil belajar siswa mengalami peningkatan dari siklus yaitu siklus I (52,00%) dengan nilai tertinggi 80 dan nilai terendah 50, siklus II (72,00%) dengan nilai tertinggi 86 dan nilai terendah 58, siklus III (92,00%) dengan nilai tertinggi 92 dan nilai terendah 70. Sedangkan nilai rata-rata kelas pada siklus I 71,60, Siklus II 74,48 dan Siklus III 81,04. Kesimpulan dari penelitian ini adalah model pembelajaran kooperatif STAD dapat berpengaruh terhadap motivasi belajar Siswa SMP Negeri 1 Jayapura tahun 2022, serta model pembelajaran ini dapat mengingkatkan hasil belajar siswa kelas IX.B SMP Negeri 1 Jayapura